Controlled growth of uniform and dense perovskite layers on SnO2 via interface passivation by PbS quantum dots - Liu, Yulin; Bae, Sumin; Lee, Seongha; Wang, Anqi; Jung, Youngsoo; Lee, Doh-Kwon; Lee, Jung-Kun (Wiley, 2024)
Formamidinium lead iodide (FAPbI(3)) and SnO2 are a promising pair of halide perovskite and electron transport layer (ETL). However, FAPbI(3) and SnO2 have inherent problems such as high crystallization temperature of FAPbI(3) and surface defects of SnO2 like oxygen vacancies. They cause low crystallinity, non-uniform grain growth, and more interface defects, leading to carrier recombination and leakage current. The passivation of the interface between FAPbI(3) and SnO2 is an effective process to address these materials issues. Herein, a dual role of lead sulfide (PbS) quantum dots (QDs) in the interface passivation is explored. PbS QDs which are introduced to the interface between FAPbI(3) and ETL, link to Sn-dangling bonds of SnO2 ETLs and anchor the iodine atoms of FAPbI(3). This changes considerably lower nonradiative recombination, achieve a better energetic alignment between ETL and PbI3, and facilitate electron extraction, leading to a power conversion efficiency of 21.66%.